If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 6y = -18 Solving 5x + 6y = -18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 5x + 6y + -6y = -18 + -6y Combine like terms: 6y + -6y = 0 5x + 0 = -18 + -6y 5x = -18 + -6y Divide each side by '5'. x = -3.6 + -1.2y Simplifying x = -3.6 + -1.2y
| -7x-2y=52 | | 2x^2-2304=0 | | 3+10=80-4 | | 4x+6y=-26 | | (8x+2)-4=18 | | 331x+6=7 | | 13+5= | | 18q=-11 | | q+13=61 | | -5x+49=-8(x-8) | | 8x-110=2x-14 | | 3+2x=x-5 | | 11z^2=-18 | | s+9=37 | | 2+3m= | | b^2-4b-b+4= | | w-8=-2 | | Y=x^2+4x+8 | | 3x*(2x+5)-(x+3)*(3x-1)=1 | | 11z^2+54=36 | | 10x+80=100 | | (3*4)n-9n=39 | | 5.23-(-9.1)= | | X^2=8x-20 | | r^2+4r+6r+24= | | -9.82+(-15.7)= | | m-3=40 | | 12+5=6+23 | | 2x+x+3+x=180 | | X*(x-7)=8 | | 5(b-6)= | | 74+114= |